Assessing Colonization’s Historic and Enduring Impact on Native American Food Culture from an Adult Education Perspective - Angela Kissel (Adult Education Research Conference, 2023)
The purpose of this Research Roundtable is to connect pre- and post-colonization adult education discourse to the historic and continued preservation of Native American food culture.
Keywords: adult education; food culture; Indigenous learning; Native American; Tribal Critical Race Theory